Historiography of industrialization in Nigeria: 1914–1960 (2018)
The historiography of industrialization in Nigeria has a rich but confused literature. Scholars from various disciplinary orientations have engaged this subject matter from perspectives that have complexified the idea and concept of industrialization in a colonial state. This study interrogates the various perspectives of intellectual inquiry on industrialization of colonial Nigeria and argues that although industries and industrial activities existed in pre-colonial and colonial Nigeria, industrialization between 1914 and 1960, as portrayed by a number of scholars, was a farce. Thus, the interrogation of theoretical and historical explanation of industrialization by scholars as one of the important components of colonial historiography seems to have been neglected. The paper submits that the historical process of colonial Nigeria made industrialization of Nigeria as a colony impossible because the colonialists used Nigeria as an important instrument that sustained the development and industrialization of Britain.